Effect of "Iran's Health System Evolution" And "Tariff Change" based on relative values book on Performance of Obstetrics and Gynecology Department: A case study in a Big Hospital - Hosein Ebrahimipour; Samira Olyani; Alireza Rezazadeh; Ali Khorsand Vakilzadeh; Somayeh Fazaeli; Mina Jafari; Arezoo Shabanifar; Mehdi Yousefi (Mashhad University of Medical Sciences, 2017)
Introduction: Health system evolution plan has been of main corrections in in Iran's health system in the last previous years. Due to the importance of these interventions on the economic and performance of the hospital, this study was performed with aim to determine the effect of health system evolution plan and Tariff change based on relative values book on the performance of obstetrics and gynecology department in Imam Reza hospital in Mashhad. Methods: This cross-sectional descriptive study was conducted by Activity Based Costing in obstetrics and gynecology department of Imam Reza hospital in Mashhad in 2013-2015. For economic-performance analysis of obstetrics and gynecology department, three categories were used including: data related to cost, data related to income, and performance indexes. Data were extracted by data gathering forms and were analyzed using descriptive statistics by Excel Software and statistical descriptive methods (mean, standard deviation, percentage, ...). Results: Total income of this department has increased respectively by 54% and 75% after health system evolution and tariff change. The highest increase of income has related to operating room after tariff change (128%). After both health system evolution and tariff change, total expenditure of this department has increased respectively by 3% and 79%. Cesarean section rate has decreased about 2/3% after evolution. Conclusion: Evolution plan has positive effect on the performance and financial indicators of obstetrics and gynecology department of Imam Reza hospital. This effect was not equal among revenue and expenditure items.